Exploring the Model of Women Silence in Universities - Leila Lotfi Dehkhargani; Yaghoob Maharati (پژوهش‌های مدیریت عمومی, 2022)
AbstractThe Importance of addressing women's organizational silence It is important to emphasize that professional women working in the organization decide to remain silent and block the knowledge-sharing process. In order to extract the main components and influences on women's organizational silence, semi-structured interviews were used and in-depth interviews with 20 people including female university professors, group managers and specialists (male and female) in the university using purposive sampling method. In the present study, using the data foundation method, in the open coding stage, 6 pivotal categories, 30 concepts and 668 codes were extracted. Findings from this study show that the main reason for women's silence in the organization is "masculine structure" and "learned helplessness" by women.IntroductionSilence is one of the issues that organizations are constantly involved in, but due to the complex nature of this issue, the absence of dissent is often considered as the absence of the issue. The aim of this study was to achieve a model in the field of women's organizational silence in the university with using the Grounded Theory. Addressing women's organizational silence is important because professional women who work at university are expected to use their knowledge in line with the organization's goals decide to remain silent and block the knowledge sharing process.Case studyTo develop our study, we focused on one international public university. The university under study gave researchers the opportunity to examine the most influential factors in context in their study. In terms of size, the university is one of the largest comprehensive universities in Iran. In terms of connection with the academic environment, the research university is an international university that offers its educational services to international students. All these features have a high level of educational quality that can make the study of the silence of female teachers meaningful.Materials and MethodTo extract the main components and influences on women's organizational silence, observation and semi-structured interviews have been used and interviews with 20 people including university professors, group managers and specialists (male and female) in the university using purposive sampling method. It has been done deeply. In the present study, using the Grounded Theory method, 41 concepts were extracted in the open coding stage.Discussion and ResultsFindings from this study show that the main reason for women's silence in the organization is the masculine structure and learned helplessness by women who have gradually learned over time that commenting and talking about organizational issues are often ignored by the system.ConclusionThis context has strong and multifaceted influencing forces on how the organization is structured, what women’s role is in society, men and women’s relationships, and how they may communicate with one another, and how women view themselves, which all determines whether women have the nous and confidence to speak up.